Tectonic controls on the thermal evolution of the Cape Smith Thrust Belt - St-Onge, M.; Lucas, S. (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1989)
Summary Reimbrication of the internal part ol the Cape Smith Thrust Belt has resulted in the development of two distinct structural-metamorphic domains. In a southern (regular-sequence thrusting) domain, thermal peak metamorphism occurred after deformation,while in a northern (out-of-sequence thrusting) domain, it occurred during deformation(/.e., re-imbrication). The interactions of tectonic and thermal processes have been studied using three methods: (1) qualitative evaluation of the timing between mineral growth and deformation; (2) analytical P-T paths from growth-zoned garnets; and (3) numerical modelling of vertical heat conduction. Analytical P-T paths suggest that uplift in the regular-sequence domain resulted primarily from erosion and isostatic unloading.In contrast, P-T paths in the out-of-sequence domain indicate that the northern portion of the thrust belt experienced faster unroofing relative to the regular-sequence domain.This has been attributed to both ramping of the out-of-sequence thrusts at deeper structural levels and possibly to extensional faulting at higher structural levels. Field and thin-section observations on the timing of metamorphism coupled with numerical modelling suggests that the thermal peak metamorphism documented in the regular-sequence domain is a consequence of the emplacement of the out-of-sequence thrust stack.